Electrocorticography During Deep Brain Stimulation Surgery: Safety Experience From 4 Centers Within the National Institute of Neurological Disorders and Stroke Research Opportunities in Human Consortium. Issue 5 (11th February 2021) - Sisterson, Nathaniel D; Carlson, April A; Rutishauser, Ueli; Mamelak, Adam N; Flagg, Mitchell; Pouratian, Nader; Salimpour, Yousef; Anderson, William S; Richardson, R Mark
Abstract: BACKGROUND: Intraoperative research during deep brain stimulation (DBS) surgery has enabled major advances in understanding movement disorders pathophysiology and potential mechanisms for therapeutic benefit. In particular, over the last decade, recording electrocorticography (ECoG) from the cortical surface, simultaneously with subcortical recordings, has become an important research tool for assessing basal ganglia-thalamocortical circuit physiology. OBJECTIVE: To provide confirmation of the safety of performing ECoG during DBS surgery, using data from centers involved in 2 BRAIN (Brain Research through Advancing Innovative Neurotechnologies) Initiative-funded basic human neuroscience projects. METHODS: Data were collected separately at 4 centers. The primary endpoint was complication rate, defined as any intraoperative event, infection, or postoperative magnetic resonance imaging abnormality requiring clinical follow-up. Complication rates for explanatory variables were compared using point biserial correlations and Fisher exact tests. RESULTS: A total of 367 DBS surgeries involving ECoG were reviewed. No cortical hemorrhages were observed. Seven complications occurred: 4 intraparenchymal hemorrhages and 3 infections (complication rate of 1.91%; CI = 0.77%-3.89%). The placement of 2 separate ECoG research electrodes through a single burr hole (84 cases) did not result in a significantly different rate of complications, compared to placement of a single electrode (3.6% vs 1.5%; P = .4). Research data were obtained successfully in 350 surgeries (95.4%). CONCLUSION: Combined with the single report previously available, which described no ECoG-related complications in a single-center cohort of 200 cases, these findings suggest that research ECOG during DBS surgery did not significantly alter complication rates.